Odpowiedzi

  • adaz
  • Początkujący
2009-10-28T22:18:07+01:00
A) x4-1 = (x2-1)(x2+1)=(x-1)(x+1)(x2-1)
b) x4-16= (x2-4)(x2+4)=(x-2)(x+2)(x2+4)
c) x4-4 = (x2-2)(x2+2)=(x-pierw. z 2)(x+pierw. z 2)(x2+2)
d) 81x4-1= (9x2-1)(9x2+1)=(3x-1)(3x+1)(9x2+1)
e) ...=(6x2-4)(6x2+4)=(pierw z 6x-2)(pierwz6x+2)(6x2+4)

jak na moje to tak będzie :)
2009-10-28T22:19:20+01:00
X⁴-1=(x²+1)(x²-1)=(x²+1)(x+1)(x-1)
x⁴-16=(x²+4)(x²-4)=(x²+4)(x+2)(x-2)
x⁴-4x=(x²+2)(x²-2)=(x²+4)(x+√2)(x-√2)
81x₄-1=(9x²+1)(9x²-1)=(9x²+4)(3x+1)(3x-1)
36x₄-16=(6x²+4)(6x²-4)=(6x²+4)(√6x+2)(√6x-2)
2 5 2